Behavior and Knowledge of Outgoing Thai Travelers Related to Medicinal Use - Supapaan, Teeraporn; Pitchayajittipong, Chonladda; Jantan, Thansiri; Putsri, Pornpimol (Iraqi Journal of Pharmaceutical Sciences, 2024)
Consultation with a healthcare professional before to travel is the basis of travel medicine. Those who received pre-travel advice from health experts exhibited lower risk behavior. This study aimed to identify outgoing Thai travelers’ behavior and knowledge regarding medicinal use when traveling. A cross-sectional survey of Thai nationals traveling abroad was conducted via a self-administered online questionnaire. The analyzed data was collected from February 2020 to June 2020. A descriptive statistic was used for the data analysis. Seven hundred people agreed to take part in this study. Most of them were female and aged 51-60 years old. The most popular destinations among the respondents were located in Asia, followed by Europe. The top five destination countries were Japan, China, Vietnam, Laos and Germany. A preferred source of information on pre-travel health consultation was the internet (43.51%). Most of the respondents did not have travel vaccinations (82.29%). Over-the-counter drugs were the most common medication carried by the respondents. Many of the outgoing Thai travelers had a good (41.29%) to excellent (46.86%) level of behavior related to medicinal use both before and during their journeys. Many participants reported that they checked the expiration date and the appearance of the medicine. Age exhibited a significant relationship with respondents’ behavior. Numerous respondents had an excellent level of knowledge related to medicinal use in terms of their medicines’ stability and storage, its use and administration, and medical laws. Gender, marital status, income, and immunization before travel had a significant relationship with the respondents’ knowledge. Most of respondents obtained health-related information prior to their travels via the internet. Most participants had great level of health behavior and medicinal use knowledge.